Sesquiterpenoids From the Antarctic Fungus Pseudogymnoascus sp. HSX2#-11 - Shi, Ting; Li, Xiang-Qian; Zheng, Li; Zhang, Ya-Hui; Dai, Jia-Jia; Shang, Er-Lei; Yu, Yan-Yan; Zhang, Yi-Ting; Hu, Wen-Peng; Shi, Da-Yong (Frontiers in Microbiology, 2021)
The fungal strains Pseudogymnoascus are a kind of psychrophilic pathogenic fungi that are ubiquitously distributed in Antarctica, while the studies of their secondary metabolites are infrequent. Systematic research of the metabolites of the fungus Pseudogymnoascus sp. HSX2#-11 led to the isolation of six new tremulane sesquiterpenoids pseudotremulanes A–F (1–6), combined with one known analog 11,12-epoxy-12β-hydroxy-1-tremulen-5-one (7), and five known steroids (8–12). The absolute configurations of the new compounds (1–6) were elucidated by their ECD spectra and ECD calculations. Compounds 1–7 were proved to be isomeride structures with the same chemical formula. Compounds 1/2, 3/4, 1/4, and 2/3 were identified as four pairs of epimerides at the locations of C-3, C-3, C-9, and C-9, respectively. Compounds 8 and 9 exhibited cytotoxic activities against human breast cancer (MDA-MB-231), colorectal cancer (HCT116), and hepatoma (HepG2) cell lines. Compounds 9 and 10 also showed antibacterial activities against marine fouling bacteria Aeromonas salmonicida. This is the first time to find terpenoids and steroids in the fungal genus Pseudogymnoascus.